Pesan Moral Islami Komik Ulong sebagai Media Dakwah: Analisis Semiotika - Nur'aziez, Fazar Zain; Fatoni, Uwes (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2022)
This paper aims to describe the representations, objects, and interpreters in the Ulong comic strip as a medium for da'wah, as well as to find out the Islamic moral messages contained in it. The research method uses descriptive methods and semiotic analysis of the episodes of the Ulong comic strip on Instagram social media. The results show that the Ulong comic strip is a comic strip that functions to spread da'wah and contains Islamic moral messages such as an appeal not to be arrogant, the negative impact of gibah, maintaining trustworthiness, not exaggeration or israf, the negative impact of disobedience to parents, ups and downs faith, and an appeal to be careful of istidraj. Keywords : Strip Comic, Medium for Da’wah, Islamic Moral Messages